2016
DOI: 10.1016/j.ridd.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-syndrome comparison of real-world executive functioning and problem solving using a new problem-solving questionnaire

Abstract: Background. Individuals with neurodevelopmental disorders like Williams syndrome andDown syndrome exhibit executive function impairments on experimental tasks (Lanfranchi, Jerman, Dal Pont, Alberti, & Vianello, 2010;Menghini, Addona, Costanzo, & Vicari, 2010), but the way that they use executive functioning for problem solving in everyday life has not hitherto been explored. The study aim is to understand cross-syndrome characteristics of everyday executive functioning and problem solving. Results. The rated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…Both behavioral and pharmaceutical interventions are also being piloted to improve cognitive outcomes in individuals with DS [44][45][46][47][48][49][50][51]. Research on individuals with DS has frequently focused on between-group differences in comparison to other individuals with intellectual disability [52][53][54][55][56][57]. This focus has helped identify the unique cognitive phenotype common in individuals with DS.…”
Section: Cognitive Development and Independencementioning
confidence: 99%
“…Both behavioral and pharmaceutical interventions are also being piloted to improve cognitive outcomes in individuals with DS [44][45][46][47][48][49][50][51]. Research on individuals with DS has frequently focused on between-group differences in comparison to other individuals with intellectual disability [52][53][54][55][56][57]. This focus has helped identify the unique cognitive phenotype common in individuals with DS.…”
Section: Cognitive Development and Independencementioning
confidence: 99%
“…Findings from studies using the BRIEF have indicated that adolescents and young adults with WS evidence considerable difficulty with EF (Hocking et al 2015;Camp et al 2016). Camp et al (2016) reported that adolescents and young adults with WS evidenced poorer performance on every scale than did similarly aged individuals with DS matched for nonverbal ability. Using the BRIEF-Adult (Roth et al 2005), Hocking et al (2015 found that for adults with WS, behaviour and emotion regulation skills were significantly stronger than metacognitive skills.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties in EF are very common among individuals with neurodevelopmental disorders (Pennington & Ozonoff 1996), including fragile X syndrome (Schmitt et al 2019), Down syndrome (DS; Lee et al 2015;Udhnani et al 2020), individuals with intellectual disability (ID) of mixed aetiology (Memisevic & Sinanovic 2014) and Williams syndrome (WS; Hocking et al 2015;Camp et al 2016). The aim of the present study was to characterise the EF of a large sample of children and adolescents with WS based on the Behavior Rating Inventory of Executive Function-2 (BRIEF-2; Gioia et al 2015) and to address the relations between EF and intellectual ability, adaptive behaviour, attention deficit/hyperactivity (ADH) problems and anxiety problems.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple factors that contribute to poor academic performance in a college setting (e.g., time management skills, organization skills, study skills; Green & Rabiner, 2012; Simon-Dack, Rodriguez, & Marcum, 2016); however, those specific difficulties are not diagnostic of ADHD (APA, 2013). Often considered associated with executive function, these issues are not specific to ADHD (e.g., Camp, Karmiloff-Smith, Thomas, & Farran, 2016) and may present in conjunction with comorbid disorders (e.g., Anastopoulos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%